Investigating the relationship between job characteristics and job stress among barista workers in Kuala Lumpur/ Nur Farahain Zulkifli ... [et al.] - Zulkifli, Nur Farahain; Mohamad Saber, Joesri; Azmi, Nurul Aziemah; Salim, Azlan; Razali, Mohamad Azli (Universiti Teknologi MARA, Sabah, 2024)
Baristas in the café industry often face high levels of job stress due to long hours, customer interactions, and complex tasks. However, research on the specific job characteristics contributing to this stress remains limited. This study aims to explore the relationship between job characteristics—task identity, skill variety, task significance, autonomy, and feedback—and job stress among baristas in Kuala Lumpur, Malaysia, using Hackman and Oldham's Job Characteristics Model (JCM) as the theoretical framework. A cross-sectional survey was conducted with 218 baristas from various cafés, and the data were analysed using Pearson correlation and multiple regression analyses. The findings revealed that autonomy and task identity significantly reduced job stress, while task significance contributed to increased stress levels. This study contributes to the academic literature by applying the JCM to the under-researched café industry, providing insights into how job design influences employee stress. The study suggests that café managers can mitigate job stress by enhancing job autonomy, providing diverse tasks, and offering regular feedback. However, limitations include convenience sampling and self-reported data, which may affect the generalizability and accuracy of the results. Future research should include longitudinal studies with more diverse samples and explore additional factors such as social support and work life balance. These findings have theoretical implications for understanding job stress in service industries and practical implications for improving workplace well-being and business sustainability in cafés.